Unveiling the Evolutionary History of European Vipers and Their Venoms From a Multi‐Omic Approach - Adrián Talavera; Marc Palmada‐Flores; Fernando Martínez‐Freiría; Gabriel Mochales‐Riaño; Bernat Burriel‐Carranza; Maria Estarellas; Daniel Fernández‐Guiberteau; Álvaro Camina; Sylvain Ursenbacher; Judit Vörös; Bálint Halpern; Davinia Pla; et al. (Molecular Ecology, 2025)
Snake genomes attract significant attention from multiple disciplines, including medicine, drug bioprospection, and evolutionary biology. However, genomic research within the Viperidae family has mostly focused on the subfamily Crotalinae, while the true vipers (Viperinae) have largely been overlooked. European vipers ( Vipera ) have been the subject of extensive research due to their phylogeographic and ecological diversification, as well as their venoms. Nevertheless, phylogeography and systematics in this genus have primarily relied on biased information from mitochondrial genes, which fail to capture the likely effects of introgression and are prone to biases. On the other hand, venom research in this group has been conducted predominantly through proteomics alone. In this study, we generated chromosome‐level genome assemblies for three Vipera species and whole‐genome sequencing data for 94 samples representing 15 Vipera lineages. This comprehensive dataset allowed us to disentangle the phylogenomic relationships of this genus, affected by mito‐nuclear discordance and pervaded by ancestral introgression. Population‐level analyses in the Iberian Peninsula, where the three oldest lineages within Vipera meet, revealed signals of recent adaptive introgression between old‐diverged and ecologically dissimilar species, whereas chromosomal rearrangements isolate species occupying similar niches. Finally, using transcriptomic and proteomic data, we characterised the Vipera toxin‐encoding genes, in which opposing selective forces were unveiled as common drivers of the evolution of venom as an integrated phenotype.

Coexistence field trials between MON810 and conventional maize in Mallorca as a basis for a regional regulatory proposal based on scientific evidence in the times of genome editing - Juan Antonio Vives-Vallés; Maria Corujo; Maria Pla; Jeroni Galmés (Transgenic Research, 2024)
This paper reports the first coexistence field trials between transgenic and conventional maize carried out under Mediterranean island conditions. Their purpose was to assess the local validity of pollen barriers and sowing delays as coexistence strategies as a basis for a regional regulation on the subject. Two field trials were performed in two agricultural states of Alcudia and Palma, in Mallorca (Spain). In the first one, two adjacent plots were synchronously sown with conventional and transgenic maize, respectively. In the second trial, the previous design was replicated, and two additional plots sown with GM maize were added, paired with their respective conventional recipient plots sown 2 and 4 weeks later. All conventional plots were located downwind from their respective GM plots. Of the two conventional plots in sowing synchrony, only one of them required a 2.25 m pollen barrier to meet the 0.9% labeling threshold. A 4-week sowing delay between GM and non-GM plots proved to be enough to keep the GM content of the recipient plots below the legal threshold. However, with a 2-week sowing delay additional coexistence measures such as pollen barriers might be needed, as suggested in the literature. Results are consistent with previous research conducted in the northeast of Spain, thus validating in the island’s agroclimatic conditions a model successfully tested in that peninsular region which allows to accurately estimate the need and width of pollen barriers. The results presented here could perhaps be extrapolated to other islands, coastal areas, and regions with stable prevailing winds during the maize flowering season.

Measurements of sound propagation in Mars' lower atmosphere - Baptiste Chide; Xavier Jacob; Andi Petculescu; Ralph D. Lorenz; Sylvestre Maurice; Fabian Seel; Susanne Schröder; Roger C. Wiens; Martin Gillier; Naomi Murdoch; Nina L. Lanza; Tanguy Bertrand; et al. (Earth and Planetary Science Letters, 2023)

Correction to: Lack of adverse effects in subchronic and chronic toxicity/carcinogenicity studies on the glyphosate-resistant genetically modified maize NK603 in Wistar Han RCC rats - Pablo Steinberg; Hilko van der Voet; Paul W. Goedhart; Gijs Kleter; Esther J. Kok; Maria Pla; Anna Nadal; Dagmar Zeljenková; Radka Aláčová; Júlia Babincová; Eva Rollerová; Soňa Jaďuďová; et al. (Archives of Toxicology, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Cocaine-Induced Preference Conditioning: a Machine Vision Perspective - V. Javier Traver; Filiberto Pla; Marta Miquel; Maria Carbo-Gas; Isis Gil-Miravet; Julian Guarque-Chabrera (Neuroinformatics, 2019)

Lack of adverse effects in subchronic and chronic toxicity/carcinogenicity studies on the glyphosate-resistant genetically modified maize NK603 in Wistar Han RCC rats - Pablo Steinberg; Hilko van der Voet; Paul W. Goedhart; Gijs Kleter; Esther J. Kok; Maria Pla; Anna Nadal; Dagmar Zeljenková; Radka Aláčová; Júlia Babincová; Eva Rollerová; Soňa Jaďuďová; et al. (Archives of Toxicology, 2019)

Genetic characterization of the Asian clam species complex (Corbicula) invasion in the Iberian Peninsula - Luis Peñarrubia; Rosa-Maria Araguas; Oriol Vidal; Carles Pla; Jordi Viñas; Nuria Sanz (Hydrobiologia, 2017)

One-year oral toxicity study on a genetically modified maize MON810 variety in Wistar Han RCC rats (EU 7th Framework Programme project GRACE) - Dagmar Zeljenková; Radka Aláčová; Júlia Ondrejková; Katarína Ambrušová; Mária Bartušová; Anton Kebis; Jevgenij Kovrižnych; Eva Rollerová; Elena Szabová; Soňa Wimmerová; Martin Černák; Zora Krivošíková; et al. (Archives of Toxicology, 2016)

Proposed criteria for the evaluation of the scientific quality of mandatory rat and mouse feeding trials with whole food/feed derived from genetically modified plants - Kerstin Schmidt; Janine Döhring; Christian Kohl; Maria Pla; Esther J. Kok; Debora C. M. Glandorf; René Custers; Hilko van der Voet; Jutta Sharbati; Ralf Einspanier; Dagmar Zeljenková; Jana Tulinská; et al. (Archives of Toxicology, 2016)

High CO2 concentration as an inductor agent to drive production of recombinant phytotoxic antimicrobial peptides in plant biofactories - Cristina Ruiz; Maria Pla; Nuri Company; Jordi Riudavets; Anna Nadal (Plant Molecular Biology, 2016)

Identification of 246 microsatellites in the Asiatic clam (Corbicula fluminea) - Luis Peñarrubia; Rosa-Maria Araguas; Carles Pla; Nuria Sanz; Jordi Viñas; Oriol Vidal (Conservation Genetics Resources, 2015)

Ninety-day oral toxicity studies on two genetically modified maize MON810 varieties in Wistar Han RCC rats (EU 7th Framework Programme project GRACE) - Dagmar Zeljenková; Katarína Ambrušová; Mária Bartušová; Anton Kebis; Jevgenij Kovrižnych; Zora Krivošíková; Miroslava Kuricová; Aurélia Líšková; Eva Rollerová; Viera Spustová; Elena Szabová; Jana Tulinská; et al. (Archives of Toxicology, 2014)

Proteomic analysis of MON810 and comparable non-GM maize varieties grown in agricultural fields - Anna Coll; Anna Nadal; Michel Rossignol; Pere Puigdomènech; Maria Pla (Transgenic Research, 2011)

Stability of the MON 810 transgene in maize - Jose Luis La Paz; Maria Pla; Nina Papazova; Pere Puigdomènech; Carlos M. Vicient (Plant Molecular Biology, 2010)

Natural variation explains most transcriptomic changes among maize plants of MON810 and comparable non-GM varieties subjected to two N-fertilization farming practices - Anna Coll; Anna Nadal; Rosa Collado; Gemma Capellades; Mikael Kubista; Joaquima Messeguer; Maria Pla (Plant Molecular Biology, 2010)

Gene expression profiles of MON810 and comparable non-GM maize varieties cultured in the field are more similar than are those of conventional lines - Anna Coll; Anna Nadal; Rosa Collado; Gemma Capellades; Joaquima Messeguer; Enric Melé; Montserrat Palaudelmàs; Maria Pla (Transgenic Research, 2009)

Effect of volunteers on maize gene flow - Montserrat Palaudelmàs; Gisela Peñas; Enric Melé; Joan Serra; Jordi Salvia; Maria Pla; Anna Nadal; Joaquima Messeguer (Transgenic Research, 2009)

Lack of repeatable differential expression patterns between MON810 and comparable commercial varieties of maize - Anna Coll; Anna Nadal; Montserrat Palaudelmàs; Joaquima Messeguer; Enric Melé; Pere Puigdomènech; Maria Pla (Plant Molecular Biology, 2008)

A Microarray-based Detection System for Genetically Modified (GM) Food Ingredients - Serge Leimanis; Marta Hernández; Sophie Fernández; Francine Boyer; Malcolm Burns; Shirin Bruderer; Thomas Glouden; Neil Harris; Othmar Kaeppeli; Patrick Philipp; Maria Pla; Pere Puigdomènech; et al. (Plant Molecular Biology, 2006)

Assessment of Real-time PCR Based Methods for Quantification of Pollen-mediated Gene Flow from GM to Conventional Maize in a Field Study - Maria Pla; José-Luis La Paz; Gisela Peñas; Nora García; Montserrat Palaudelmàs; Teresa Esteve; Joaquima Messeguer; Enric Melé (Transgenic Research, 2006)

A 10-kDa class-CI sHsp protects E. coli from oxidative and high-temperature stress - Anna Jofr; Marisa Molinas; Maria Pla (Planta, 2003)

A Specific Real-Time Quantitative PCR Detection System for Event MON810 in Maize YieldGard® Based on the 3′-Transgene Integration Sequence - Marta Hernández; Maria Pla; Teresa Esteve; Salomé Prat; Pere Puigdomènech; Alejandro Ferrando (Transgenic Research, 2003)